Deteksi Bovine Herpesvirus-1 Secara Immunohistokimia pada Membran Korioallantois Telur Ayam Berembrio (IMMUNOHISTOCHEMISTRY DETECTION OF BOVINE HERPESVIRUS-1 IN CORIOALLANTOIC MEMBRANE OF CHICKEN EMBRYONATED EGG) - Kristianingrum, Yuli Purwandari; Tabbu, Charles Rangga; Sutrisno, Bambang; Widyarini, Sitarina; ., Kurniasih; Untari, Tri; Kusumawati, Asmarani (Jurnal Veteriner; Vol 16 No 4 (2015), 2016)
Infectious Bovine Rhinotracheitis (IBR) is caused by Bovine Herpes virus-1 in the cattle. The clinicalsigns demonstrate depression, anorexia, swelling of the vulva, redness of the vestibule, pustule and ulceron the vaginal mucosal. Based on previous research, IBR virus from the nasal swab could be grown inchorio-allantoic membrane of embryonated chicken eggs. This study aim was to confirm whether IBR virusin cattle could be grown in embryonated chicken eggs as a substitute for cell culture. A total of five nasalswab samples from the cows that were positive for IBR infection (diagnosed by Polymerase Chain Reactionand cell culture) were inoculated on the chorio-allantois membrane of embryonated chicken eggs.Observation of lesions performed at 3-5 days after inoculation. Re-inoculation (passage) was done threetimes. Pock characteristic lesions were observed on the corioallantoic membrane with the size of 5-7 mm,rounded shape, opaque edge, with necrosis in the central area. Furthermore, pock lesions were processedfor hematoxylin and eosin staining and immuno-histochemistry. The result of hematoxylin and eosinstaining showed that the formation of intranuclear inclusion bodies and vacuolization of the epithelial cellof membrane was observed. Immuno-histochemistry staining showed positive reaction for antibodiesagainst BHV-1 in the epithelial cells membrane. In conclusion, embryonated chicken eggs could be usedas a medium for detection of IBR.
Keywords: bovine herpes virus-1, pock lesions, chorio-allantoic membrane